Queer Identities, Queer Content and Library Classification: Is 'Queering the Catalogue' the Answer?. Issue 2 (3rd April 2021) - McAuliffe, Bethany
ABSTRACT: This article explores and reviews some of the literature surrounding the issue of traditional classification methods for queer identities and content in libraries. Particular attention is given to Emily Drabinski's article, ' Queering the Catalogue ' and what her proposed methods might look like in practice. The review was conducted through an analysis of relevant literature, especially paying attention to resources which came from the critical librarianship perspective. The literature addressed in this review considered two major approaches: the first involved methods that were part of cataloguing processes, and the second were concerned with complementary library practice. Further to these two approaches, Drabinski uses queer theory to propose a different method in which original classification terminology is used to ensure an acknowledgement of all relevant discourse. My conclusion from this review is that there is no one universal solution and all libraries should critically engage with their collection in relation to the safety and information needs of their community before making any decisions. In the future, there is a need for more librarians to consider their role critically so that they can make informed decisions about cataloguing and classification regarding access to queer identities and content. IMPLICATIONS FOR BEST PRACTICE Provides an analysis of the seminal critical librarianship piece ' Queering the Catalogue ' (Drabinski, 2013 ) Introduces contested concepts within traditional library classification methods, especially in reference to queer identities and content Highlights the important role that librarians can play in classifying queer identities and content within their library